High-Latitude Cold Ion Outflow Inferred From the Cluster Wake Observations in the Magnetotail Lobes and the Polar Cap Region - Li, Kun; André, Mats; Eriksson, Anders; Wei, Yong; Cui, Jun; Haaland, Stein (Frontiers in Physics, 2021)
Cold ions with low (a few eV) thermal energies and also often low bulk drift energies, dominate the ion population in the Earth’s magnetosphere. These ions mainly originate from the ionosphere. Here we concentrate on cold ions in the high latitude polar regions, where magnetic field lines are open and connected to the magnetotail. Outflow from the ionosphere can modify the dynamics of the magnetosphere. In-situ observations of low energy ions are challenging. In the low-density polar regions the equivalent spacecraft potential is often large compared to cold ion energies and the ions cannot reach the spacecraft. Rather, a supersonic ion flow creates an enhanced wake. The local electric field associated with this wake can be used to detect the drifting cold ions, and this wake technique can be used for statistical studies. In this paper, we review some of the key results obtained from this technique. These results help us to understand how cold ionospheric outflow varies with various conditions of solar activities and the Earth’s intrinsic magnetic field.